A Review On Membrane Desalination Process in Water Treatment. Issue 1 (1st December 2022) - Aljumaily, Mustafa Mohammed; Alshami, Abeer W.; Ismael, Bashar H.; Hameed, Mohammed Majeed; AlOmar, Mohamed Khalid; Hussain, Intesar R.; hameed, Mohammed saleh; Alsalhy, Qusay F.; Alsaadi, Mohammed A.
Abstract: Desalination is being used on a much larger scale as a result of the rising scarcity of freshwater. Desalination plant energy usage, however, continues to be a problem. Inherently appealing, the use of renewable energy sources has been the subject of numerous research. Membrane processes are indeed attracting a great deal of interest due to their economic viability and capacity to be scaled up. This article offers a cutting-edge review of membrane processes related to renewable energies for desalinating seawater and brackish water. Reverse osmosis, membrane distillation, and electrodialysis are examples of membrane processes. They are combined with renewable energies like hydrostatic pressure, waves, solar, wind, and wind. The key findings in this field include principles, plant design and implementation, mathematical models, and economic viability, are presented in this article.